2018
DOI: 10.3171/2017.5.spine161370
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of 3 surgical strategies for adult spinal deformity with mild to moderate sagittal imbalance

Abstract: OBJECTIVESurgical treatment of adult spinal deformity (ASD) is an effective endeavor that can be accomplished using a variety of surgical strategies. Here, the authors assess and compare radiographic data, complications, and health-related quality-of-life (HRQoL) outcome scores among patients with ASD who underwent a posterior spinal fixation (PSF)–only approach, a posterior approach combined with lateral lumbar interbody fusion (LLIF+PSF), or a posterior approach com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 32 publications
4
47
0
Order By: Relevance
“…Significantly earlier PJK onset was observed in the OLIF51 group (8.6 months) than in the TLIF51 group (26.3 months), which was also earlier than that of previous reports (18.6-34.8 months) [38,39]. Other reports found that the incidence of PJK could be reduced by minimally invasive lumbar interbody fusion and percutaneous fixation, which suggests that other factors may have accelerated PJK development after cMIS with OLIF at L5-S1 in our study [40,41]. Faundez et al reported an exaggerated upper lumbar lordosis resulting in junctional failure [39].…”
Section: Discussionsupporting
confidence: 59%
“…Significantly earlier PJK onset was observed in the OLIF51 group (8.6 months) than in the TLIF51 group (26.3 months), which was also earlier than that of previous reports (18.6-34.8 months) [38,39]. Other reports found that the incidence of PJK could be reduced by minimally invasive lumbar interbody fusion and percutaneous fixation, which suggests that other factors may have accelerated PJK development after cMIS with OLIF at L5-S1 in our study [40,41]. Faundez et al reported an exaggerated upper lumbar lordosis resulting in junctional failure [39].…”
Section: Discussionsupporting
confidence: 59%
“…It is different from cMISS in terms of paraspinal muscle dissection. In ASD with moderate sagittal deformity, a hybrid surgical approach involving a combination of MISS interbody fusion and open posterior approach has been used in the alternation of traditional open posterior-only approach [ 9 , 10 ].…”
Section: Surgical Techniquementioning
confidence: 99%
“…Wang [ 33 ] reported significant improvement of sagittal balance with multilevel facet osteotomies and MISS TLIF in addition to percutaneous screw fixation for ASD. Anterior lumbar interbody fusion (ALIF) offers several advantages over LLIF, including direct decompression of neural foramina, accessibility to L5–S1, less mobilization of the psoas muscle, resection of the ALL, wide discectomies, and insertion of wedge-shaped lordotic grafts that result in greater segmental lordosis restoration in the lower lumbar spine compared with TLIF [ 10 , 34 ]. However, it does carry the risks related to mobilization of the abdominal viscera and large vessels.…”
Section: Lumbosacral Interbody Fusion Optionmentioning
confidence: 99%
“…Disk degeneration is the main cause of ASD, and a correction at the interbody space is one of the most appropriate surgical methods [3,4]. Lateral lumbar interbody fusion (LIF) is widely used for ASD [5][6][7]. This technique, which was recently introduced, uses a lateral trans-psoas approach to the disk, which involves less invasive surgical exposure, avoids the major vessels, and permits the placement of large interbody cages that allow the correction of the deformity [6][7][8].…”
Section: Introductionmentioning
confidence: 99%